2008
DOI: 10.1097/nmd.0b013e318162aa9c
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Subjective Quality of Life in People With Schizophrenia

Abstract: Quality of life (QOL) is an important outcome for people with schizophrenia, but most previous studies of its correlates have had small sample sizes or explored a limited number of variables. We conducted an analysis of the baseline data from the European Schizophrenia Cohort (EuroSC) study, a naturalistic investigation of people with schizophrenia living in France, Germany, and the United Kingdom (N = 1208). German participants had the highest subjective QOL. Country of residence, depression, accommodation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 42 publications
1
28
1
Order By: Relevance
“…Consistent results of 3 studies (Table 1) were published in unemployed patients who revealed higher scores in total psychopathology, negative symptoms, bizarre behavior, blunted affect, and depression compared to employed subjects [35][36][37]. Improved quality of life among subjects in competitive employment was found in several studies [38][39][40]. This type of employment may also be beneficial for general well-being [35], self-esteem [36], network sizes [41], satisfaction with leisure [35,36] and decline in use of outpatient services [42].…”
Section: Ijomeh 2015;28(3) 414supporting
confidence: 73%
“…Consistent results of 3 studies (Table 1) were published in unemployed patients who revealed higher scores in total psychopathology, negative symptoms, bizarre behavior, blunted affect, and depression compared to employed subjects [35][36][37]. Improved quality of life among subjects in competitive employment was found in several studies [38][39][40]. This type of employment may also be beneficial for general well-being [35], self-esteem [36], network sizes [41], satisfaction with leisure [35,36] and decline in use of outpatient services [42].…”
Section: Ijomeh 2015;28(3) 414supporting
confidence: 73%
“…In the European Schizophrenia Cohort Study which was a naturalistic investigation of people with schizophrenia living in 3 European countries, correlates of QOL identified include; depression, accommodation status and employment. 39 Similar QOL correlates have also been identified among Nigerian patients with schizophrenia. 26,27 Poor social support has been identified as an important determinant of poor subjective QOL among Nigerian patients.…”
Section: Discussionmentioning
confidence: 51%
“…We used the European Schizophrenia Cohort (EuroSC) – a naturalistic 2-year follow-up of a cohort of 1,208 European schizophrenia patients [14]. Indeed, the EuroSC cohort has been extensively used in past research, which focused on investigating treatment efficacy [15], patients’ quality of life [1618], employment [19], social contact [20,21] and subjective feelings of security and safety [22], as well as assessing caregiver burden [23] and quantifying direct health care costs associated with managing the disease [24,25]. …”
Section: Introductionmentioning
confidence: 99%